Epidemiological characteristics and trends of a Nationwide measles outbreak in Mongolia, 2015-2016 - Oyunchimeg Orsoo; Yu Mon Saw; Enkhbold Sereenen; Buyanjargal Yadamsuren; Ariunsanaa Byambaa; Tetsuyoshi Kariya; Eiko Yamamoto; Nobuyuki Hamajima (BMC, 2019)
Abstract Background Mongolia was one of the four countries that received a measles-elimination certificate from the World Health Organization Regional Office for the Western Pacific in 2014. Following the outbreaks in many countries including China, a large measles outbreak occurred in Mongolia in 2015. This study reports 2015-2016 measles outbreak incidence, mortality, and complications, according to time, geographical distribution, and host characteristics. Methods The epidemiological characteristics and trends of measles outbreak were analyzed using the Mongolian national surveillance data reported to the Center for Health Development, Ministry of Health, from January 2015 to December 2016. Results In total, 23,464 cases of measles including eight deaths were reported in 2015, and 30,273 cases of measles including 132 deaths were reported in 2016, which peaked in June 2015 and March 2016, respectively. Majority of the cases were reported from Ulaanbaatar (35,397, 65.9%). The highest attack rates were 241 per 10,000 population in Darkhan-Uul aimag, and 263 per 10,000 population in Ulaanbaatar. Measles-related death, nosocomial infection, and complications were most frequent among children aged < 1 year. Conclusions Following no reports of measles since 2011, a large nationwide outbreak occurred in Mongolia, despite the high vaccination coverage in the past. The highest incidence rate was reported in Ulaanbaatar city, and Umnugovi aimag in 2015 and Darkhan-Uul aimag in 2016. The most affected age group were aged < 1 year and those aged 15-24 years. Mortality cases were prominent among children aged < 1 year who were not eligible for vaccination. A systematic vaccination strategy is required to prevent another measles outbreak.